Characterization of the Response of the Arabidopsis Response Regulator Gene Family to Cytokinin - D'Agostino, Ingrid B. (American Society of Plant Physiologists, 2000)
We examined the expression of a family of Arabidopsis response regulators (ARR) and found that the steady-state levels of RNA for most are elevated very rapidly by cytokinin. Using nuclear run-on assays we demonstrated that this increase in ARR transcript levels in response to cytokinin is due, at least in part, to increased transcription. The start site of transcription for the ARR5 gene was identified using primer extension analysis. A DNA fragment comprised of 1.6 kb upstream of the ARR5 transcript start site conferred cytokinin-inducible gene expression when fused to a β-glucuronidase reporter, confirming that the transcription rate of ARR5 is elevated by cytokinin. This reporter construct was also used to examine the spatial pattern of ARR5 expression. The highest levels of expression were observed in the root and shoot apical meristems, at the junction of the pedicle and the silique, and in the central portion of mature roots. The expression of ARR5 in the apical meristems was confirmed by whole mount in situ analysis of seedlings and is consistent with a role for cytokinin in regulating cell division in vivo.